ANALISA RASIO DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Rosalia Noviani (2020)
This research was conducted aiming to analyze the effect of liquidity, leverage, and profitability in predicting financial distress conditions in mining sector companies listed on the Indonesia Stock Exchange (BEI) in the 2016-2018 period. The dependent variable in this study is financial distress with the Altman Z-Score measurement model while the independent variable of this study is liquidity with the current ratio (CR) calculation model, leverage with the debt to assets ratio (DAR) calculation model, and profitability with the return on assets (ROA) calculation model. The sampling technique uses a purposive sampling method. Selection of sample from 49 mining companies listed on the IDX in the 2016-2018 period resulted in 42 companies being accepted. Data analysis using Microsoft Excel 2016 and hypothesis testing using Logistic Regression Analysis using the E-views 10.0 program. The results of testing are obtained (1) liquidity has no effect on financial distress, (2) leverage has a positive effect on financial distress, and (3) profitability has a negative effect on financial distress.